KONTRAK BUILD OPERATE TRANSFER SEBAGAI PERJANJIAN KEBIJAKAN PEMERINTAH DENGAN PIHAK SWASTA - Adha, Lalu Hadi (Faculty of Law, Universitas Jenderal Soedirman, 2011)
BOT (Build Operate Transfer) as a form of agreement held by the government policy with private parties is a legal act by the agency or the State administration officials who make public policy as the object of the agreement. Although inherent in him as a body or public official, the government in implementing the contractual relationship with another party (private) legal act is not governed by public law, but based on the laws and regulations of civil law (privaat recht), as the case of legislation that underlie civil legal actions carried out a body of citizens and civil law. The research shows that in a contractual relationship, the government as a party to the BOT contracts have no equal footing with their counterparts. This will be discussed in more depth in the study of law with the approach of juridical normative or study in a BOT contract as an agreement policy. Key words : BOT contract, agreement, policy